Developing A Module For Islamic Foresight As A Tool For Shared Prosperity And Social Well-being - Norfadhilah Binti Mohamad Ali; Hendun Abd. Rahman Shah; Fadhlina Alias; Muhammad Nizam Awang; Nisar Mohammad Ahmad (Zes Rokman Resources, 2024)
Non-Indexed Publication